Last resort or key resource? Women workers from the Nazi-occupied Soviet territories, the Reich labour administration and the German war effort - Harvey, Elizabeth (Cambridge University Press, 2016)
Foreign labour was an essential resource for the Nazi war economy: by September 1944, around six million civilian labourers from across Europe were working in the Reich. Any initial readiness on the part of the peoples of Nazi-occupied Europe to volunteer for work in the Reich had quickly dissipated as the harsh and often vicious treatment of foreign workers became known. The abuse and exploitation of foreign forced labourers by the Nazi regime is well documented. Less well understood is why women formed such a substantial proportion of the labour recruited or forcibly deported from occupied eastern Europe: in September 1944, a third of Polish forced labourers and just over over half of Soviet civilian forced labourers were women. This article explores the factors influencing the demand for and the supply of female labour from the Nazi-occupied territories of the Soviet Union, particularly after the appointment of Fritz Sauckel as Plenipotentiary for Labour in March 1942. It explores the attitudes of labour officials towards these women workers and shows how Nazi gender politics and the Nazi hierarchy of race intersected in the way they were treated.